Europäische Werberegulierungssysteme am Beispiel geschlechterdiskriminierender Wirtschaftswerbung - Koch, Leonie Josefine (Bild und Recht - Studien zur Regulierung des Visuellen, 2022)
In the current debate on gender-appropriate and non-discriminatory commercial communication, this study takes a comparative legal look at the different legal and self-regulatory instruments of the European advertising regulation systems. With the inclusion of social science, cognitive psychology and communication theory, the study not only examines the existing national regulations in their respective cultural context, but also considers new European developments, social influencing factors and possible harmonization approaches in the highly controversial field of gender-discriminatory commercial advertising.